2011
DOI: 10.1371/journal.pone.0029492
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 15 Levels in Serum May Predict a Severe Disease Course in Patients with Early Arthritis

Abstract: BackgroundInterleukin-15 (IL-15) is thought to be involved in the physiopathological mechanisms of RA and it can be detected in the serum and the synovial fluid of inflamed joints in patients with RA but not in patients with osteoarthritis or other inflammatory joint diseases. Therefore, the objective of this work is to analyse whether serum IL-15 (sIL-15) levels serve as a biomarker of disease severity in patients with early arthritis (EA).Methodology and ResultsData from 190 patients in an EA register were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 35 publications
1
52
0
1
Order By: Relevance
“…IL-17 levels decreased following disease onset, while MCP-1, MIP-1α, GM-CSF and G-CSF were increased significantly in pre-patients compared with control subjects, and a number of other cytokines became increased significantly versus controls in the 3 years prior to disease onset (IL-2R, IL-1β, IL-9, IL-10, eotaxin, GM-CSF). Other studies have also demonstrated increased IL-15 in early arthritis, which may be associated with disease severity [30,31]. The increase in serum IL-4 demonstrated in EIA and RA is perhaps surprising.…”
Section: Discussionmentioning
confidence: 97%
“…IL-17 levels decreased following disease onset, while MCP-1, MIP-1α, GM-CSF and G-CSF were increased significantly in pre-patients compared with control subjects, and a number of other cytokines became increased significantly versus controls in the 3 years prior to disease onset (IL-2R, IL-1β, IL-9, IL-10, eotaxin, GM-CSF). Other studies have also demonstrated increased IL-15 in early arthritis, which may be associated with disease severity [30,31]. The increase in serum IL-4 demonstrated in EIA and RA is perhaps surprising.…”
Section: Discussionmentioning
confidence: 97%
“…IL-15 was consistently detectable and elevated in the serum of patients with early stage OA, compared with end-stage patients undergoing total knee replacement [Scanzello et al 2009]. Serum IL-15 detected by a proteomic approach was associated with the presence and progression of radiographic OA [Gonzalez-Alvaro et al 2011]. IL-15 may stimulate MMP production and recruitment or survival of CD8+ T cells within the OA joint.…”
Section: Soluble Catabolic and Inflammatory Mediatorsmentioning
confidence: 97%
“…IL-15 induces NK cells activation, measured either by direct cytotoxicity, antibody-dependent cellular cytotoxicity or cytokines production [36]. It has also been shown that IL-15 stimulates the functional maturation of DCs and IL-15 enhances the ability of DCs to activate CD8+ cells and NK cells by up-regulating the expression of co-stimulatory molecules and IFN-γ [37,38]. In addition, IL-15 enhances phagocytosis and protects from apoptosis of neutrophils, and affects mast cell proliferation [37].…”
Section: Il-15 Bioactivitymentioning
confidence: 99%